Tolterodine : a New Bladder Selective Muscarinic Receptor Antagonist - Tantisira, Mayuree H. (Journal of Basic and Applied Pharmacology, 2015)
Tolterodine is a new competitive muscarinic receptor antagonist recently approved for the treatment of overactive bladder with symptoms of urinary frequency, urgency or urge incontinence. Though tolterodine is a nonsubtype selective antimuscarinic agent, it exhibits favorable selectivity for the urinary bladder over salivary glands both in vitro and in vivo studies. It is well absorbed after oral administration and exhibits high first-pass metabolism. Two hepatic metabolic pathways, oxidation and N-dealkylation, are mediated by the cytochrome P450(CYP) isoforms 2D6 and 3A4, respectively. Urinary excretion of metabolites accounts for approximately 80% of the administered dose. Pharmacokinetic profile of tolterodine is linear over the dose 1-4 mg and does not appear to be affected by age or gender. The active 5-hydroxymethyl metabolite formed by CYP 2D6 shows rather similar pharmacodynamic and pharmacokinetic profiles, except for binding ability to plasma protein, to its parent compound. In patients with overactive bladder, tolterodine significantly reduces clinically relevant end points such as number of micturition and number of incontinence episode/day while increasing the average volume voided. Therapeutic efficacy of tolterodine is maintained during long term treatment. As might be expected from its pharmacological profile, the principal adverse effect of tolterodine is dry mouth. An optimal efficacy/side effect profile is obtained with tolterodine at a dosage of 1-2 mg twice daily. Comparatively, tolterodine and oxybutynin (5 mg tid.) are equivalent in terms of efficacy. However, tolterodine is better tolerated than oxybutynin ’with respect to the incidence and severity of dry mouth. No clinically relevant ECG changes or significant adverse effect on the central nervous system have been noted with tolterodine.